Inside the virtual product : how organizations create knowledge through software - D'Adderio, Luciana, 1967- (Cheltenham ; Northampton, MA : Edward Elgar, 2004)
The book represents an in-depth and systematic attempt to characterize the fundamental influence of software over the processes that underpin an organization's ability to create and manage knowledge. Scholars and students interested in innovation, technological change and information technology, and managers in software and other hi-tech industries will find this an insightful and highly rewarding study.
Includes bibliographical references (p. 217-224) and index.
oif 16/02/15
Loan
Keywords: New products -- Data processing..; Knowledge management -- Data processing; Information technology